Biết 4x(4x+3)A=-4x.(-5x).(4x+3) . Khi đó biểu thức A là: 23/07/2021 Bởi aihong Biết 4x(4x+3)A=-4x.(-5x).(4x+3) . Khi đó biểu thức A là:
$4x(4x+3).A=-4x.(-5x).(4x+3)$ $(16x^2+12x).A=20x^2.(4x+3)$ $(16x^2+12x).A=80x^3+60x^2$ $A=(80x^3+60x^2):(16x^2+12x)$ $A=5x$ Vậy biểu thức $A=5x$ Bình luận
Đáp án: Giải thích các bước giải: `4x(4x+3)A=-4x.(-5x).(4x+3)` `=>4x(4x+3).A=4x(4x+3).5x` `=>A=5x` Học tốt Bình luận
$4x(4x+3).A=-4x.(-5x).(4x+3)$
$(16x^2+12x).A=20x^2.(4x+3)$
$(16x^2+12x).A=80x^3+60x^2$
$A=(80x^3+60x^2):(16x^2+12x)$
$A=5x$
Vậy biểu thức $A=5x$
Đáp án:
Giải thích các bước giải:
`4x(4x+3)A=-4x.(-5x).(4x+3)`
`=>4x(4x+3).A=4x(4x+3).5x`
`=>A=5x`
Học tốt